Is there an association between multiple sclerosis and osteoarthritis in Germany? A retrospective cohort study of 8, 600 patients from Germany. Issue 2 (June 2021) - Jacob, Louis; Smith, Lee; Koyanagi, Ai; Haro, Josep Maria; Konrad, Marcel; Tanislav, Christian; Kostev, Karel
Objectives: The goal of this retrospective cohort study was to investigate the multiple sclerosis-osteoarthritis relationship in adults followed in general practices in Germany. Methods: Patients aged 18-70 years who were diagnosed for the first time with multiple sclerosis in one of 1, 193 general practices in Germany between 2005 and 2018 (index date) were included in this retrospective cohort study. Patients without multiple sclerosis were matched (1:1) to those with multiple sclerosis by sex, age, index year, general practice, obesity, injuries, and other types of arthritis (index date: a randomly selected visit date). The association between multiple sclerosis and the 10-year incidence of osteoarthritis was analyzed using Cox regression models. Results: There were 4, 300 patients with multiple sclerosis and 4, 300 patients without multiple sclerosis included in this study. The proportion of women was 69.3% and mean (SD) age was 43.6 (12.6) years. There was no significant association between multiple sclerosis and incident osteoarthritis in the overall sample (HR = 0.95, 95% CI: 0.83-1.09) as well as sex and age subgroups. Conclusions: Based on these findings, multiple sclerosis is not significantly associated with osteoarthritis. Further studies of longitudinal nature are warranted to corroborate or invalidate these results.